Back Cover Image. Issue 9 (16th September 2022) - Xia, Mengling; Niu, Guangda; Liu, Linyue; Gao, Runlong; Jin, Tong; Wan, Pengying; Pan, Weicheng; Zhang, Xianpeng; Xie, Zuoxiang; Teale, Sam; Cai, Zenghua; Luo, Jiajun; et al.
Abstract: Sensitive and fast detection of neutrons and gamma rays is vital for homeland security, high‐energy physics and proton therapy. However, efficient mixed‐field detection using a single material is highly challenging because fast‐neutron detectors rely on light organic scintillators, and γ‐ray detectors use heavy inorganic scintillators and semiconductors. In the cover, the authors (DOI: 10.1002/inf2.12325 ) illustrate organic‐inorganic hybrid perovskites that combine light organic cations and heavy inorganic skeletons at a molecular level to achieve unprecedented performance for mixed‐field radiation detection, so as to obtain the time information and energy information of the nuclear reaction process accurately. Abstract : Sensitive and fast detection of neutrons and gamma rays is vital for homeland security, high‐energy physics and proton therapy. However, efficient mixed‐field detection using a single material is highly challenging because fast‐neutron detectors rely on light organic scintillators, and γ‐ray detectors use heavy inorganic scintillators and semiconductors. In the cover, the authors (DOI: 10.1002/inf2.12325 ) illustrate organic‐inorganic hybrid perovskites that combine light organic cations and heavy inorganic skeletons at a molecular level to achieve unprecedented performance for mixed‐field radiation detection, so as to obtain the time information and energy information of the nuclear reaction process accurately.